2021
DOI: 10.21037/tlcr-20-420
|View full text |Cite
|
Sign up to set email alerts
|

Induction treatment in patients with stage III non-small cell lung cancer

Abstract: Stage III non-small cell lung cancer (NSCLC) comprises a highly heterogeneous group of patients defined according to the extent and localization of disease. Patients with discrete N2 involvement identified preoperatively with resectable disease are candidates for multimodal therapy either with definitive chemoradiation therapy, induction chemotherapy, or chemoradiotherapy (CTRT) followed by surgery.Neoadjuvant chemotherapy has yielded comparable survival benefit to adjuvant chemotherapy in patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Jia et al reported the e cacy and safety of neoadjuvant immunotherapy. Compared with the results of neoadjuvant chemoimmunotherapy in our meta-analysis, neoadjuvant immunotherapy has less rate of MPR (37%) and pCR (14%), a similar surgical resection rate (88%), a higher incidence of surgical complications (29%), and surgical delay rate (3%), but good tolerance of toxicity (TRAE16%) [26], this similar conclusion was also suggested in Palmero et al [27]. Results of CheckMate 816, a phase III trial, reported that the pCR was 23% and event-free survival was 31.6% in stage IIIA NSCLC, moreover, the greater bene t was seen in stage IIIA than in those with stage IB or II patients, which strongly supported our research [28].…”
Section: Discussionsupporting
confidence: 86%
“…Jia et al reported the e cacy and safety of neoadjuvant immunotherapy. Compared with the results of neoadjuvant chemoimmunotherapy in our meta-analysis, neoadjuvant immunotherapy has less rate of MPR (37%) and pCR (14%), a similar surgical resection rate (88%), a higher incidence of surgical complications (29%), and surgical delay rate (3%), but good tolerance of toxicity (TRAE16%) [26], this similar conclusion was also suggested in Palmero et al [27]. Results of CheckMate 816, a phase III trial, reported that the pCR was 23% and event-free survival was 31.6% in stage IIIA NSCLC, moreover, the greater bene t was seen in stage IIIA than in those with stage IB or II patients, which strongly supported our research [28].…”
Section: Discussionsupporting
confidence: 86%
“…Jia et al reported the efficacy and safety of neoadjuvant immunotherapy. Compared with the results of neoadjuvant chemoimmunotherapy in our meta-analysis, neoadjuvant immunotherapy has less rate of MPR (37%) and pCR (14%), a similar surgical resection rate (88%), a higher incidence of surgical complications (29%), and surgical delay rate (3%), but good tolerance of toxicity (TRAE16%) [ 26 ], this similar conclusion was also suggested in Palmero et al [ 27 ]. Results of CheckMate 816, a phase III trial, reported that the pCR was 23% and event-free survival was 31.6% in stage IIIA NSCLC, moreover, the greater benefit was seen in stage IIIA than in those with stage IB or II patients, which strongly supported our research [ 28 ].…”
Section: Discussionsupporting
confidence: 86%
“…Notably, two to four treatment cycles were administrated in most of the relevant phase II/III trials on neoadjuvant immunotherapy (15)(16)(17)20,21). Extended treatment cycles might result in the postponement of surgery, while a short course of treatment may not be sufficient for ICB to induce its effect.…”
Section: Introductionmentioning
confidence: 99%